MODERN POSSIBILITIES OF THERAPY OF TYPE 2 DIABETES MELLITUS PATIENTS. EFFECTIVENESS AND CARDIOSAFETY OF ALOGLIPTIN FROM THE POINT OF VIEW OF EVIDENCE-BASED MEDICINE - A. S. Ametov (Медицинский совет, 2017)
According to the IDF (2016) 1 of 11 adult patients suffers from diabetes mellitus (DM). The total number of diabetic patients is 415 million. By 2040, according to analysts of the International Diabetes Federation, the number of the sick increases and the disease will affect 1 in 10 people. It is extremely important to maintain all indicators of carbohydrate metabolism (fasting glucose and postprandial, HbA1c) within the target values. Currently existing recommendations are not obligatory and do not give the strict guidance on the priority use of a group of hypoglycemic drugs and other drugs. The choice of patient-orientated approach, based on the effectiveness and safety of drugs. On the basis of numerous clinical studies have proven the effectiveness and safety of Alogliptin in the treatment of patients with type 2 diabetes.